Mocaf Flour for Food Security, Stunting Alleviation, and Creative Economy: ASystem Thinking Approach - Sarasi, Vita; Yulianti, Dina; Saefulhadjar, Deny (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The rising dependence on imported wheat flour in Indonesia highlights the need for local alternatives such as Mocaf (modified cassava flour). This study explores the potential of Mocaf production in Sindangsuka Village, Garut, to strengthen food security, reduce childhood stunting, and promote the creative economy. A systems thinking approach was employed using a Causal LoopDiagram (CLD) to map and analyze the dynamic interconnections among these three domains. Data was gathered through literature review, focus group discussions (FGDs), and interviews with key local stakeholders. InsightMaker software was used to construct and simulate the CLD. The model identified reinforcing loops showing how increased Mocaf production improves local food access, supports child nutrition, and enhances household income through Mocaf-based enterprises. Triangulated validation confirmed key causal pathways linking innovation, nutrition programs, and creative economic activity. Policy leverage points include supporting agroecological practices, promoting maternal education, and expanding market access. Findings suggest that Mocafproduction can simultaneously address public health and economic development goals. By integrating Mocaf into school feeding and micro-enterprise programs, communities can reduce stunting and boost income. The updated CLD also highlights potential risks such as market saturation and environmental degradation, underscoring the need for adaptive policies. This study contributes a validated systems model for rural development, offering practical insights for policymakers. It underscores that food system resilience requires coordinated strategies that address interconnected challenges across nutrition, agriculture, and livelihoods.